Effect of Blanching Pretreatment before Drying on the Microstructure and Texture Quality of Dried Apple Slices - WANG Dong, ZHAO Yifan, DENG Zhining, SUN Haoyuan, WANG Yong, YUAN Yuejin (Shipin Kexue)
To improve the drying efficiency and quality of hot air-dried apple slices with blanching pretreatment, this study systematically evaluated the effects of two blanching pretreatments, hot water blanching and vacuum steam pulsed blanching, on the macroscopic drying performance of apple slices. The results indicated that under the conditions of 0.07 MPa vacuum, two blanching cycles, and blanching time of 3 minutes, vacuum steam pulsed blanching significantly enhanced the rehydration rate and textural quality of apple slices while reducing the drying time. Paraffin sectioning, microscopic observation and image processing were used to compare the microstructural changes of apple slices in terms of cell cross-sectional area, perimeter, equivalent diameter, cell roundness, wall roughness factor, and porosity under different branching conditions (temperature and time for hot water blanching; vacuum level, number of cycles, and time for vacuum steam pulsed blanching). The results showed that with the increase in temperature, blanching time and number of blanching cycles, apple cells exhibited changes that accelerated water evaporation during subsequent drying, thus shortening the drying time. Additionally, the relationship between microstructural parameters and rehydration ratio was fitted to a polynomial regression model. The findings of this study provide a theoretical basis for understanding the mechanisms by which vacuum steam pulsed blanching affects the microstructure and quality of dried apple slices.